The ALERT model of care for the assessment and personalized management of patients with lymphoedema. Issue 3 (6th November 2019) - Boyages, J.; Koelmeyer, L. A.; Suami, H.; Lam, T.; Ngo, Q. D.; Heydon‐White, A.; Czerniec, S.; Munot, S.; Ho‐Shon, K.; Mackie, H.
Abstract : Background: This study documents the development and evaluation of a comprehensive multidisciplinary model for the assessment and personalized care of patients with lymphoedema. Methods: The Australian Lymphoedema Education Research and Treatment (ALERT) programme originated as an advanced clinic for patients considering surgery for lymphoedema. The programme commenced liposuction surgery in May 2012 and then introduced lymph node transfer in 2013 and lymphovenous anastomosis (LVA) in 2016. An outpatient conservative treatment clinic was established in 2016. ALERT commenced investigations with indocyanine green (ICG) lymphography in late 2015, leading to the creation of a diagnostic assessment clinic offering ICG in 2017. Results: Since 2012, 1200 new patients have been referred to ALERT for assessment of lymphoedema for a total of 5043 episodes of care. The introduction of ICG lymphography in 2015 initially allowed better screening for LVA, but is now used not only to guide surgical options, but also as a diagnostic tool and to guide manual lymphatic drainage massage. The total number of new patients who attended the surgical assessment clinic to December 2018 was 477, with 162 patients (34·0 per cent) undergoing surgery. Conclusion: The ALERT programme has developed a multidisciplinary model of care for personalized lymphoedema treatment options based on clinical, imaging and ICG lymphography. Patients are selected for surgery based on several individual factors. Abstract : This study documents the development and evaluation of a comprehensive multidisciplinary model for the assessment and personalized care of patients with lymphoedema. Optimal treatment for lymphoedema? Abstract : Antecedentes: Este estudio presenta el desarrollo y valoración de un modelo multidisciplinario integral para la evaluación y atención personalizada de pacientes con linfedema. Métodos: El programa australiano de educación en investigación y tratamiento del linfedema (Australian Lymphoedema Education Research and Treatment, ALERT) se originó como un centro clínico avanzado para pacientes que consideran la cirugía como tratamiento para el linfedema. El programa se inició en mayo del 2012 con la cirugía de liposucción, introduciendo la cirugía de transferencia ganglionar (lymph node transfer, LNT) en 2013 y la anastomosis linfovenosa (lymphovenous anastomosis, LVA) en 2016. En 2016 se estableció una clínica de tratamiento conservador ambulatorio. ALERT comenzó las investigaciones con la linfografía con verde de indocianina (indocyanine green, ICG) a fines del 2015, lo que se siguió de la creación de una clínica de evaluación diagnóstica que ofrece ICG en 2017. Resultados: Desde el 2012, 1.200 pacientes nuevos han sido referidos a ALERT para la evaluación de un linfedema, con un total de 5.043 episodios atendidos. La introducción inicialmente de linfografía con ICG en 2015 permitió un mejor cribaje para LVA, pero actualmente se utiliza no solo como guía de las opciones quirúrgicas, sino también como herramienta diagnóstica y como guía del masaje de drenaje linfático manual (manual lymphatic drainage, MLD). El número total de pacientes nuevos atendidos en la clínica de evaluación quirúrgica hasta diciembre de 2018 fue de 477, con 122 pacientes (34%) tratados quirúrgicamente. El modelo tal como se ha descrito, ha atraído a pacientes de toda Australia y Nueva Zelanda. Conclusión: El programa ALERT ha desarrollado un modelo multidisciplinario de atención para las opciones de tratamiento personalizado del linfedema basado en la evaluación clínica, por imagen (MRI y LSG) y linfografía con ICG. Los pacientes se seleccionan cuidadosamente para el tratamiento quirúrgico en función de varios factores relacionados con el paciente, el tumor, los linfáticos y las opciones terapéuticas, y se someten a una evaluación detallada después de cualquier procedimiento.